Meningkatkan Motivasi Belajar Peserta Didik Dengan Menggunakan Media Modul Elektronik Di Era Revolusi Industri 4.0: (Improving Students' Learning Motivation through Electronic Module Media in the Industrial Revolution 4.0) - Zaharah Zaharah; Ade Susilowati (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
There are problems related to learning motivation that occurred in SMP Negeri 22 according to the observation conducted: passive learning environment and lack of students’ participation, readiness and engagement in learning that lead to the students’ poor academic achievement. In order to overcome the problems, the researchers in this study used electronic module due to its practicality, efficiency and interesting features that it has: audio, animation and video. Electronic module has a potential to bring abstract content into more concrete for the students, so that they might feel more motivated to learn. The purpose of this study was to determine the effect of Electronic Module Media on the stduents’ learning motivation in Class VIII E SMP Negeri 22 Jambi city. The research method applied is classroom action research. The results show that the use of electronic module media has increased the students’ motivation to learn, this can be seen from the results of the questionnaire as follows: 0% agree that the media is lacking, 16.7% agree that it is sufficiently good, 56.7% agree that it is good and 26.7% agree that it is categorized as very good and able to give a positive impact on the students’ learning outcomes on cognitive, affective and psychomotor aspect. This can be seen from the cognitive learning outcomes of the students who have completed learning that reached 86.67% with an average score of 75.3. The students successfully achieved good categories on affective and psychomotor aspects. Abstrak. Kulit singkong kurang dimanfaatkan oleh masyarakat sehingga menjadi limbah. Kulit singkong mengandung pati yang berpotensi sebagai edible coating. Tomat mudah mengalami kerusakan pasca panen sehingga kadar total fenol dan vitamin C menurun, maka perlu adanya alternatif untuk mempertahankan kadar total fenol dan vitamin C tomat dengan cara aplikasi edible coating pati kulit singkong. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh adanya aplikasi edible coating pati kulit singkong konsentrasi 1%, 2% dan 4% terhadap kadar total fenol dan kadar vitamin C tomat hari ke 3, 6 dan 12 serta mengetahui potensi hasil penelitian sebagai sumber belajar IPA SMP kelas VIII materi zat aditif. Kadar total fenol diuji menggunakan metode spektrofotometri dan kadar vitamin C menggunakan metode titrasi iodium. Hasil penelitian menunjukan kadar total fenol dan kadar vitamin C tertinggi terjadi pada hari ke 12 perlakuan edible coating 4% berturut-turut sebesar 0.0525% dan 33.2210mg/100g, maka edible coating pati kulit singkong dapat mempertahankan kadar total fenol dan vitamin C tomat dibandingkan kontrol. Hasil penelitian dapat digunakan sebagai sumber belajar IPA SMP kelas VIII materi zat aditif.